Evaluating Multiple Aspects of Educational Computer Games: Literature Review and Case Study. (7th December 2014) - Nunes Marciano, Juvane; Cunha de Miranda, Leonardo; Esteves Cunha de Miranda, Erica
Abstract : Evaluation is an important step in the life cycle of software, once through this practice it is possible to find issues that could compromise the user experience. With educational computer games, the same rule is applied. The use of educational games is increasing, and it is important to verify these tools to provide users with the most adequate learning environments. This verification can be made through the evaluation of multiple aspects of these tools. This work presents a literature review about evaluation of multiple aspects of software, followed by a more specific review focused on multiple aspects of educational computer games. Then, a case study is presented, in which an evaluation method is applied with an educational computer game, aiming to verify the positives and the issues to be improved in the game. The reviews and the description of the process to use the method intend to help and guide other researchers to choose evaluation methods that can fit their own context and needs.